Synthesis and Photoluminescence Studies on Catalytically Grown Zn1 – xMnxS Nanowires - R. Venugopal; D. Amaranatha Reddy; G. Murali1,; R.P. Vijayalakshmi; B.K. Reddy (Журнал нано- та електронної фізики)
Zn1 – xMnxS alloy nanowires with composition (x = 0.0, 0.1 and 0.3) have been successfully synthesized by a simple thermal evaporation on the silicon substrate coated with a gold film of 2 nm thickness. X-ray powder diffraction measurements reveal that as synthesized products were hexagonal wurtzite structure. The as grown nanowires have been investigated by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy Dispersive Analysis of X-rays (EDAX) and photoluminescence studies. The results reveal that the as grown nanowires consist of Zn, Mn, and S material and diameter ranging from 70 - 150 nm with lengths up to several tens of micrometers. Photoluminescence studies on Zn1 – xMnxS exhibited peaks at 600 and 613 nm for x = 0.1 and 0.3 respectively.